Answer:
[tex]C(t)=\frac{r}{k}-(\frac{r-kC_o}{k})e^{-kt}[/tex]
Explanation:
The differential equation is given as:
[tex]\frac{dC}{dt} = r- kC[/tex]
[tex]\frac{dC}{r- kC} = dt[/tex]
Taking integral of both sides; we have:
[tex]\int\limits \frac{dC}{r- kC} = \int\limits dt[/tex]
[tex]-\frac{1}{k} In(r-kC) = t+D\\In(r-kC)=-kt-kD[/tex]
[tex]r-kC=e^{-kt-kD}[/tex]
[tex]r-kC=e^{-kt}e^{-kD}[/tex]
[tex]r-kC=Ae^{-kt}[/tex]
[tex]kC=r-Ae^{-kt}[/tex]
[tex]C=\frac{r}{k}-\frac{A}{k}e^{-kt}[/tex]
[tex]C(t)=\frac{r}{k}-\frac{A}{k}e^{-kt}[/tex] ------- equation (1)
If C(0)= [tex]C_o[/tex] ; we have:
C(0)= [tex]\frac{r}{k}-\frac{A}{k}e^0[/tex] (where; A is an integration constant)
[tex]C_o = \frac{r}{k}- \frac{A}{k}[/tex]
[tex]C_o=\frac{r-A}{k}[/tex]
[tex]kC_o=r-A[/tex]
[tex]A=r-kC_o[/tex]
Substituting [tex]A=r-kC_o[/tex] into equation (1); we have;
[tex]C(t)=\frac{r}{k}-(\frac{r-kC_o}{k})e^{-kt}[/tex]